Risperidone augmentation decreases rapid eye movement sleep and decreases wake in treatment-resistant depressed patients. - Sharpley, A; Bhagwagar, Z; Hafizi, S; Whale, W; Gijsman, H; Cowen, P (2003)
BACKGROUND: The atypical antipsychotic agent risperidone has beneficial effects on mood in patients with schizophrenia. This study aimed to assess whether risperidone produced typical antidepressant-like effects in the polysomnogram of healthy subjects and in depressed patients unresponsive to antidepressant medication. METHOD: We measured the effect of a single dose of risperidone (1 mg) on the polysomnogram of 8 healthy volunteers in a placebo-controlled, double-blind, crossover design. We also measured the effects of open-label risperidone treatment (0.5-1.0 mg daily) on the polysomnogram of 8 patients meeting DSM-IV criteria for major depressive disorder who had received therapeutic doses of an antidepressant with an unsatisfactory response. Sleep was recorded at baseline and following 2 weeks of risperidone addition. RESULTS: In the healthy volunteers, risperidone significantly decreased rapid eye movement (REM) sleep (p =.04). After 2 weeks of risperidone treatment, depressed patients had significantly less wake (p =.02) and REM sleep (p =.02). Scores on depression rating scales for the depressed patients showed a significant decline (p <.05). CONCLUSION: Risperidone administration decreases REM sleep in both healthy volunteers and medication-resistant depressed patients, an action characteristic of conventional antidepressant medication. In depressed patients, risperidone also decreased wake. The utility of risperidone as an augmentation agent in depressed patients merits controlled study.